1994
DOI: 10.1183/09031936.94.07030484
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of bronchial responsiveness by forced oscillation technique in occupational epidemiology

Abstract: M Me ea as su ur re em me en nt t o of f b br ro on nc ch hi ia al l r re es sp po on ns si iv ve en ne es ss s b by y f fo or rc ce ed d o os sc ci il ll la at ti io on n t te ec ch hn ni iq qu ue e i in n o oc cc cu up pa at ti io on na al l e ep pi id de em mi io ol lo og gy y Changes in resistance (∆R 0 %), frequency dependence of resistance (∆P) and resonant frequency (∆F%) determined by the FOT were compared to the ∆FEV 1 %. Receiver operating characteristic (ROC) curves were established to determine val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…In normal subjects, resistive impedance (Rω) can be fairly well described over 4-32 Hz by a linear frequencydependent model characterized by its intercept with the ordinate axis and its slope, which is generally close to zero [1][2][3][4][5][6][7]. By contrast, in obstructive patients, Rω exhibits a negative frequency-dependence, which mostly occurs below 16 Hz, and is better described by two regression lines [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In normal subjects, resistive impedance (Rω) can be fairly well described over 4-32 Hz by a linear frequencydependent model characterized by its intercept with the ordinate axis and its slope, which is generally close to zero [1][2][3][4][5][6][7]. By contrast, in obstructive patients, Rω exhibits a negative frequency-dependence, which mostly occurs below 16 Hz, and is better described by two regression lines [8].…”
Section: Discussionmentioning
confidence: 99%
“…In normal subjects, the resistive respiratory impedance derived from this technique, appears to be a linear function of frequency over the usual range (4-32 Hz). Resistive impedance can, therefore, be characterized by two parameters, namely its intercept with the ordinate axis, which represents respiratory resistance extrapolated at zero frequency (R0), and its slope (S) which is then close to zero [1][2][3][4][5][6][7]. By contrast, in patients with airway obstruction or in subjects shown to be hyperreactive on bronchial challenge, resistive impedance displays a marked negative frequency dependence up to about 16 Hz, and at least two straight line segments are then necessary to approximate it by linear functions of frequency.…”
mentioning
confidence: 99%
“…It also appeared interesting to consider the parameters derived from respiratory reactance. Indeed, parallel variations of R0 and RF have been reported in the course of bronchial challenge tests to inhaled methacholine [22], and any increase in tissue elastance is associated with an increase in Ers, and thereby in RF. …”
Section: Discussionmentioning
confidence: 99%
“…By using the average reaction in IOS parameters and linear regression model, Wang et al 25 reported that an 80% increase in resonance frequency, 50% increase in Z 5 or R 5 , or 100% increase in X 5 could be regarded as significant. Pairon et al 26 reported an assay sensitivity of 0.75 and specificity of 0.76 for a 65% increase in total resistance for methacholine bronchial provocation test in active workers with normal baseline spirometry. They also showed that the positive threshold was 65% and 50% for elastance at 10 Hz and resonance frequency: results similar to our study.…”
Section: Discussionmentioning
confidence: 99%